The scope of Baker's law. Issue 3 (20th July 2015) - Pannell, John R.; Auld, Josh R.; Brandvain, Yaniv; Burd, Martin; Busch, Jeremiah W.; Cheptou, Pierre‐Olivier; Conner, Jeffrey K.; Goldberg, Emma E.; Grant, Alannie‐Grace; Grossenbacher, Dena L.; Hovick, Stephen M.; Igic, Boris; et al.
Summary: Baker's law refers to the tendency for species that establish on islands by long‐distance dispersal to show an increased capacity for self‐fertilization because of the advantage of self‐compatibility when colonizing new habitat. Despite its intuitive appeal and broad empirical support, it has received substantial criticism over the years since it was proclaimed in the 1950s, not least because it seemed to be contradicted by the high frequency of dioecy on islands. Recent theoretical work has again questioned the generality and scope of Baker's law. Here, we attempt to discern where the idea is useful to apply and where it is not. We conclude that several of the perceived problems with Baker's law fall away when a narrower perspective is adopted on how it should be circumscribed. We emphasize that Baker's law should be read in terms of an enrichment of a capacity for uniparental reproduction in colonizing situations, rather than of high selfing rates. We suggest that Baker's law might be tested in four different contexts, which set the breadth of its scope: the colonization of oceanic islands, metapopulation dynamics with recurrent colonization, range expansions with recurrent colonization, and colonization through species invasions.   Contents     Summary 656 I. Introduction 657 II. What is Baker's law, and how did it originate? 658 III. Mate limitation during mainland–island colonization 660 IV. Mate limitation in metapopulations 661 V. Mate limitation during species introductions and invasions 663 VI. Mate limitation during range expansions and evolution at range margins 663 VII. Pollinator limitation, the evolution of dispersal, and the scope of Baker's law 664 VIII. Conclusions and future perspectives 664   Acknowledgements 665   References 665